Location based FDS Framework - Bae Kim, Jong; Jin Bae, Myung (International Journal of Engineering and Technology, 2018)
The FDS (Fraud Detection System) is a technological approach to prevent financial accidents by detecting abnormal behavior in financial transactions. In this paper, we present system components and considerations for efficient FDS construction and operation, and propose an optimized FDS operation framework based on IT governance. In addition, we propose a model that can improve the accuracy of abnormal transaction detection by using GPS information of user. This research is expected to be an operation model for Fintech based FDS that enables safe transactions without sacrificing the convenience of customers.Â Â